Magnetic and Morphological Characterization of Magnetic Minerals from Sarimukti Landfill - Dwi Putri K Manurung; Dini Fitriani; Eleonora Agustine; Kartika Hajar Kirana; Petrus Ardi Tama (Jurnal Penelitian Pendidikan IPA, 2025)
Sarimukti landfill serves as a waste disposal site. Leachate generated from waste accumulation is discharged through pipelines into multiple retention ponds. This study aims to assess contamination levels in leachate deposits by analyzing the magnetic properties and morphology of magnetic minerals collected from four retention ponds, along with measurements of pH, EC, and TDS in the pond water. Magnetic susceptibility values range from 37.4 – 409.5 (×10⁻⁸) m³/kg, indicating ferrimagnetic mineral dominance. The  values range from 0.81% - 5.96%, where  >2% is often associated to pollutant-contaminated soils. A negative correlation between  and  suggests a minor contribution of superparamagnetic grains from pedogenesis. Scanning Electron Microscopy - Energy Dispersive Spectroscopy (SEM-EDS) analysis identifies spherule and hedral magnetic mineral shapes, with O and Fe as dominant elements and minor Ti, indicating magnetite and titanomagnetite presence. Other elements, including C, Mg, Al, Si, K, Ca, and Mn, likely originate from anthropogenic sources.